Single-cell sequencing analysis and multiple machine-learning models revealed the cellular crosstalk of dendritic cells and identified FABP5 and KLRB1 as novel biomarkers for psoriasis - Ma, Zhiqiang; An, Pingyu; Hao, Siyu; Huang, Zhangxin; Yin, Anqi; Li, Yuzhen; Tian, Jiangtian (Frontiers in Immunology, 2024)
Background: Psoriasis, a prototypical immune-mediated disorder, exhibits a pronounced penchant for extracutaneous manifestations. Despite advancements, challenges persist, including the diminishing efficacy of biologics and small-molecule targeted agents, alongside diagnosing and managing psoriasis-related comorbidities. Unraveling the underlying pathogenesis and identifying valuable biomarkers remain pivotal for diagnosing and treating psoriasis.Methods: We employed a series of bioinformatics (including single-cell sequencing data analysis and machine learning techniques) and statistical methods to integrate and analyze multi-level data. We observed the cellular changes in psoriatic skin tissues, screened the key genes Fatty acid binding protein 5 (FABP5) and The killer cell lectin-like receptor B1 (KLRB1), evaluated the efficacy of six widely prescribed drugs on psoriasis treatment in modulating the dendritic cell-associated pathway, and assessed their overall efficacy. Finally, qT-PCR, immunohistochemistry, and immunofluorescence assays were used to validate.Results: The regulatory influence of dendritic cells (DCs) on T cells through the CD70/CD27 signaling pathway emerged as a significant facet of the inflammatory response in psoriasis. Notably, FABP5 and KLRB1 exhibited substantial up-regulation and co-localization in psoriatic skin tissues and M5-induced HaCaT cells, serving as biomarkers influencing psoriasis development.Conclusion: Our study analyzed the impact of DC-T cell crosstalk in psoriasis, elucidated the characterization of two biomarkers, FABP5 and KLRB1, in psoriasis, and highlighted the promise and value of tofacitinib in psoriasis therapy targeting DCs.